Opportunity and challenges using the cloud computing in the case of Malaysian higher education institutions - Arfan Shahzad; Abd Ghani Golamdin; Noor Azizi Ismail (The International Journal of Management Science and Information Technology (IJMSIT), 2016)
In this 21st century, the demand for cloud computing is increasing globally from all levels of industry including higher education institutions. In this study, we discuss the benefits and challenges involved in adopting cloud computing in the context of higher education institutions in Malaysia. It is expected that adopting the modern technology of cloud computing will reduce the cost of IT-based solution and services as well as of the ICT Infrastructure. Cloud computing enables rapid setup of ICT Infrastructure, more secure intra-organization connection and faster Web deployment. It provides greater opportunity for students and lecturers to build e-portal for sharing knowledge and learning tools. It will also help in an efficient and cost-effective manner, the internationalization of research projects. Many issues still remain to be addressed before cloud computing can be successfully implemented in the higher education sector. The importance of cloud computing will be outlined in this paper.
Keywords: 650; Cloud computing; benefits; challenges; higher education institution; IT